Environmental gradients predict the ratio of environmentally acquired carotenoids to self‐synthesised pteridine pigments. (4th August 2021) - Stuart‐Fox, Devi; Rankin, Katrina J.; Lutz, Adrian; Elliott, Adam; Hugall, Andrew F.; McLean, Claire A.; Medina, Iliana
Abstract: Carotenoids are important pigments producing integument colouration; however, their dietary availability may be limited in some environments. Many species produce yellow to red hues using a combination of carotenoids and self‐synthesised pteridine pigments. A compelling hypothesis is that pteridines replace carotenoids in environments where carotenoid availability is limited. To test this hypothesis, we quantified concentrations of five carotenoid and six pteridine pigments in multiple skin colours and individuals from 27 species of agamid lizards. We show that environmental gradients predict the ratio of carotenoids to pteridines; carotenoid concentrations are lower and pteridine concentrations higher in arid environments with low vegetation productivity. Both carotenoid and pteridine pigments were present in all species, but only pteridine concentrations explained colour variation among species and there were no correlations between carotenoid and pteridine pigments with a similar hue. These results suggest that in arid environments, where carotenoids are likely limited, species may compensate by synthesising more pteridines but do not necessarily replace carotenoids with pteridines of similar hue. Abstract : We present a comparative analysis of environmental drivers of pigment concentrations in lizards. Our results support a scenario where environmental carotenoid availability influences the relative concentrations of dietary carotenoids and self‐synthesised pteridine pigments used to generate yellow to red skin colours. This indicates that environmental gradients can shape the ecology and evolution of animal colouration by altering the relative cost of environmentally acquired and self‐synthesised pigments.